Case Report: Cerebral Nocardiosis Caused by Nocardia cyriacigeorgica Detected by Metagenomics in an Apparently Immunocompetent Patient - Courbin, Virginie; Riller, Quentin; Amegnizin, Jean-Louis; Gricourt, Guillaume; Demontant, Vanessa; Fihman, Vincent; Angebault, Cecile; Mahevas, Matthieu; Gaube, Géraldine; Coutte, Laëtitia; Pawlotsky, Jean-Michel; Lepeule, Raphaël; et al. (Frontiers in Immunology, 2022)
We report a case of meningoencephalitis due to Nocardia cyriacigeorgica diagnosed with metagenomics, while all the standard methods were negative. This diagnosis made adaptation of antimicrobial treatment possible and led to the discovery of a rare acquired immunodeficiency syndrome.